Nutrition and dietary pattern in relation to blood status and physical work capacity among Swedish conscripts during basic combat training - Fabian Taube; Mats Navrén; Örjan Ekblom; Ingrid Larsson (BMJ Military Health, 2026)
Introduction Adequate nutrition and regular meal patterns are essential for maintaining metabolic health as well as optimal physical and cognitive function. Military conscripts represent a particularly vulnerable population due to the high physical and cognitive demands placed on them during basic combat training (BCT). We sought to identify the relationship between nutrition and dietary patterns before and during BCT and health-related variables. Methods A total of 96 female and 129 male conscripts completed questionnaires at baseline and after 5 months, assessing dietary habits and general health. Haemoglobin and ferritin were measured both at baseline and after 5 months of BCT. Physical work capacity was assessed at baseline, including an incremental multistage shuttle run test and a neuromuscular multitest. Results Vegetarian dietary patterns were associated with lower baseline ferritin (β=−20.5, p=0.011) but a greater increase in haemoglobin during BCT (β=4.50, p=0.026). Less frequent breakfast consumption was associated with lower baseline physical work capacity (β=−0.32, p=0.015). Over a 5-month period, conscripts reporting less frequent consumption of full meal portions had lower baseline physical work capacity (β=−0.33, p=0.019) and higher odds of injury or overuse symptoms (OR 2.33, p=0.015) and missed training (OR 1.85, p=0.047). Not eating enough in relation to individual needs was associated with a smaller increase in haemoglobin (β=−7.38, p